Edukasi Budidaya dan Pemindahan Koloni Alami Lebah Tanpa Sengat (Galo-galo) di Nagari Tigo Balai, Kecamatan Matur, Kabupaten Agam - Henny Herwina; Jasmi Jasmi; Eli Ratni; Alvia Rahmi; Joy Prima; Gelvin Apria Ikhsan; Pooja Angela Mendoza; Miftahul Ilmi (Warta Pengabdian Andalas, 2023)
Community development provides empowerment and opportunities for the community to explore the potential and resources around them to increase their productivity and welfare. Empowerment can be done in many fields, such as agriculture and animal husbandry. The potential for community empowerment in agriculture and animal husbandry, which is multiplying effects, is the cultivation of stingless bees (Galo-galo). One of the areas with great potential for developing this cultivation was Nagari Tigo Balai Matur, Agam Regency, West Sumatra. This activity aims to facilitate the community regarding Galo-galo cultivation in the environment around the Nagari Tigo Balai Matur community, Agam Regency. The activity was conducted in May-August 2023, using counselling methods (education and direct facilitation/mentoring) with pilot practices in field activities. The results obtained from this activity were an increase in public knowledge about stingless bee farming (Galo-galo meliponiculture), the transfer of 21 Tetragonula sp. bee colonies to a maintenance box, and the appearance of very high public interest in galo-galo cultivation based on local potential.